Activation of neurokinin-III receptors modulates human atrial TASK-1 currents - Wiedmann, Felix Tobias; Paasche, Amelie; Nietfeld, Jendrik; Kraft, Manuel; Meyer, Anna L.; Warnecke, Gregor; Karck, Matthias; Frey, Norbert; Schmidt, Constanze (Journal of molecular and cellular cardiology, 2023)
Rationale - The neurokinin-III receptor was recently shown to regulate atrial cardiomyocyte excitability by inhibiting atrial background potassium currents. TASK-1 (hK2P3.1) two-pore-domain potassium channels, which are expressed atrial-specifically in the human heart, contribute significantly to atrial background potassium currents. As TASK-1 channels are regulated by a variety of intracellular signalling cascades, they represent a promising candidate for mediating the electrophysiological effects of the Gq-coupled neurokinin-III receptor. - Objective - To investigate whether TASK-1 channels mediate the neurokinin-III receptor activation induced effects on atrial electrophysiology. - Methods and results - In Xenopus laevis oocytes, heterologously expressing neurokinin-III receptor and TASK-1, administration of the endogenous neurokinin-III receptor ligands substance P or neurokinin B resulted in a strong TASK-1 current inhibition. This could be reproduced by application of the high affinity neurokinin-III receptor agonist senktide. Moreover, preincubation with the neurokinin-III receptor antagonist osanetant blunted the effect of senktide. Mutagenesis studies employing TASK-1 channel constructs which lack either protein kinase C (PKC) phosphorylation sites or the domain which is regulating the diacyl glycerol (DAG) sensitivity domain of TASK-1 revealed a protein kinase C independent mechanism of TASK-1 current inhibition: upon neurokinin-III receptor activation TASK-1 channels are blocked in a DAG-dependent fashion. Finally, effects of senktide on atrial TASK-1 currents could be reproduced in patch-clamp measurements, performed on isolated human atrial cardiomyocytes. - Conclusions - Heterologously expressed human TASK-1 channels are inhibited by neurokinin-III receptor activation in a DAG dependent fashion. Patch-clamp measurements, performed on human atrial cardiomyocytes suggest that the atrial-specific effects of neurokinin-III receptor activation on cardiac excitability are predominantly mediated via TASK-1 currents.